2018
DOI: 10.3389/fpls.2018.01047
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Effect of Increased Plant Density on Canopy Morphology and Stalk Lodging Risk

Abstract: Plants react to the environment and to management interventions by undergoing architectural and structural modifications. A field trial was conducted in China in 2016 to study the effects of the plant population on morphological development of the maize canopy. The main objectives of the current study were (i) to characterize the effects of increased plant density on canopy morphology and stalk lodging and (ii) to explore the relationships between organ morphology and stalk lodging. The field experiment was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 61 publications
2
25
0
1
Order By: Relevance
“…Under high planting densities, mutual shading of plants disturbs the light environment of crop which reduced the photosynthetic activities and carbohydrates accumulation in the stem that leads to lodging easily [ 25 , 129 ]. It has been witnessed that planting densities were negatively correlated with the lodging resistance of stem; however, high plant population had promoted the lodging and lower grain production [ 129 , 130 , 131 , 132 ]. In addition, optimum planting densities could expand the structure of the plant population and provide a better light environment, enhanced photosynthetic rate and ultimately increased the lodging resistance of stem [ 74 , 133 ].…”
Section: Agro-techniques For the Management Of Lodging Stressmentioning
confidence: 99%
“…Under high planting densities, mutual shading of plants disturbs the light environment of crop which reduced the photosynthetic activities and carbohydrates accumulation in the stem that leads to lodging easily [ 25 , 129 ]. It has been witnessed that planting densities were negatively correlated with the lodging resistance of stem; however, high plant population had promoted the lodging and lower grain production [ 129 , 130 , 131 , 132 ]. In addition, optimum planting densities could expand the structure of the plant population and provide a better light environment, enhanced photosynthetic rate and ultimately increased the lodging resistance of stem [ 74 , 133 ].…”
Section: Agro-techniques For the Management Of Lodging Stressmentioning
confidence: 99%
“…At present, planting high density has already become one of the key measures to excavate the potential high yield of crops among the various cultivation methods [42,43]. Previous studies have found that planting density was significantly negatively correlated with the stem lodging resistance, excessively high planting density results in lodging, and lower grain yield, which seriously affected the normal growth and development of crops and yield [44][45][46]. Suitable field planting density could improve the structure of the plant population and create a better environment for plants to make full use of light energy, promote photosynthesis, improve the lodging resistance of stem, and increase yield [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…A 2-year experiment was carried out at Mengcheng Agricultural Sci-Tech Park, Anhui province, China (latitude 33°09′N, Longitude 116°33′E) with a lime concretion black soil type in 2016 and 2018. The data in 2016 were reported in Sher et al (2018) , and the data in 2018 are reported for the first time. Five PD treatments with three replicates designed to induce differing levels of interplant competition were used, and they are 4.5, 6, 7.5, 9, and 15 plants m –2 (referred to as PD4.5, PD6, PD7.5, PD9, and PD15, respectively).…”
Section: Methodsmentioning
confidence: 99%